Maintenance of dominance status is necessary for resistance to social defeat stress in Syrian hamsters - Morrison, Kathleen E. (2014)
Resilience is an active process that involves a discrete set of neural substrates and cellular mechanisms and enables individuals to avoid some of the negative consequences of extreme stress. We have previously shown that dominant individuals show less stress-induced changes in behavior compared to subordinates using a conditioned defeat model in male Syrian hamsters (Mesocricetus auratus). To rule out pre-existing differences between dominants and subordinates, we examined whether 14 days of dominance experience is required to reduce the conditioned defeat response and whether the development of conditioned defeat resistance correlates with defeat-induced neural activation in select brain regions. We paired hamsters in daily 5-min aggressive encounters for 1, 7, or 14 days and then exposed animals to 3, 5-min social defeat episodes. The next day animals received conditioned defeat testing which involved a 5-min social interaction test with a non-aggressive intruder. In separate animals brains were collected after social defeat for c-Fos immunohistochemistry. We found that 14-day dominants showed a decreased conditioned defeat response compared to 14-day subordinates and controls, while 1-day and 7-day dominants did not differ from their subordinate counterparts. Also, the duration of dominance relationship was associated with distinct patterns of defeat-induced neural activation such that only 14-day dominants showed elevated c-Fos immunoreactivity in the ventral medial prefrontal cortex, medial amygdala, and lateral portions of the ventral medial hypothalamus. Our data suggest that resistance to social stress develops during the maintenance of dominance relationships and is associated with experience-dependent neural plasticity in select brain regions.